2010
DOI: 10.1186/1471-2229-10-220
|View full text |Cite
|
Sign up to set email alerts
|

Light intensity affects RNA silencing of a transgene in Nicotiana benthamianaplants

Abstract: BackgroundExpression of exogenous sequences in plants is often suppressed through one of the earliest described RNA silencing pathways, sense post-transcriptional gene silencing (S-PTGS). This type of suppression has made significant contributions to our knowledge of the biology of RNA silencing pathways and has important consequences in plant transgenesis applications. Although significant progress has been made in recent years, factors affecting the stability of transgene expression are still not well unders… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(46 citation statements)
references
References 58 publications
0
34
0
1
Order By: Relevance
“…Although in most of them light effect on silencing was not clearly isolated from that of temperature (Nethra et al, 2006;Vaucheret et al, 1997) recently, Kotakis et al (2010) investigated solely the role of light intensity in physiological ranges on RNA silencing. They used as a system N. benthamiana transgenic lines engineered to express GFP, which exhibited spontaneously silencing at different frequencies and of different spreading intensities.…”
Section: Lightmentioning
confidence: 99%
“…Although in most of them light effect on silencing was not clearly isolated from that of temperature (Nethra et al, 2006;Vaucheret et al, 1997) recently, Kotakis et al (2010) investigated solely the role of light intensity in physiological ranges on RNA silencing. They used as a system N. benthamiana transgenic lines engineered to express GFP, which exhibited spontaneously silencing at different frequencies and of different spreading intensities.…”
Section: Lightmentioning
confidence: 99%
“…Environmental effects on transgene expression have been observed between field and greenhouse-grown Gladiolus, 33 in Chrysanthemum grown under different temperatures, 34 and in Nicotiana exposed to different light intensities. 35 Of the four major allergens analyzed in this study, Ara h 1 and Ara h 2 constitute approximately 12−16 and 5.9−9.3% of the total seed protein, respectively. 12,13 Because there was no statistically significant difference in the extractable seed protein of field-grown transgenic compared to non-transgenic lines across generations, decreasing Ara h 2 and Ara h 6 proteins in seeds must be tempered by compensation with multiple proteins, including slight increases in Ara h 1 and Ara h 3.…”
Section: ■ Results and Discussionmentioning
confidence: 73%
“…It was shown in an earlier study that transgene silencing may occur either in the primary transformant or in subsequent generations in an unpredictable, de novo manner due to differential methylation patterns of either one or both strands of transgene DNA (Fu et al 1999). It has also been shown that transgene silencing pattern could be influenced by the environmental factors (Kotakis et al 2010).…”
Section: Discussionmentioning
confidence: 99%